2021
DOI: 10.3389/fvets.2021.656810
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Research in Bovine Mastitis

Abstract: Bovine mastitis is one of the most important diseases in the dairy industry and has detrimental impact on the economy and welfare of the animals. Further, treatment failure results in increased antibiotic use in the dairy industry, as some of these mastitis cases for unknown reasons are not resolved despite standard antibiotic treatment. Chronic biofilm infections are notoriously known to be difficult to eradicate with antibiotics and biofilm formation could be a possible explanation for mastitis cases that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 106 publications
1
38
0
1
Order By: Relevance
“…None of the isolates were sensitive for all antimicrobials, an aspect also observed by others [ 34 , 35 , 36 ]. In the present research, all 14 strains tested showed the multiple resistance phenomenon, as follows: six strains (42.9%) to five antimicrobials, three strains (21.4%) to six antimicrobials, two strains (14.3%) to eight antimicrobials, two strains (14.3%) to nine antimicrobials and one strain (7.1%) to ten antimicrobials.…”
Section: Resultssupporting
confidence: 78%
“…None of the isolates were sensitive for all antimicrobials, an aspect also observed by others [ 34 , 35 , 36 ]. In the present research, all 14 strains tested showed the multiple resistance phenomenon, as follows: six strains (42.9%) to five antimicrobials, three strains (21.4%) to six antimicrobials, two strains (14.3%) to eight antimicrobials, two strains (14.3%) to nine antimicrobials and one strain (7.1%) to ten antimicrobials.…”
Section: Resultssupporting
confidence: 78%
“…In fact, biofilm are responsible for up to 80% of all human chronic and recurrent infections [ 35 , 36 ]. However, in veterinary medicine, only a few studies report the role of biofilm in animal infections [ 37 , 38 , 39 ]. In one of the most studied animal infections, mastitis, it has already been demonstrated that chronic and recurrent bovine mastitis share similar characteristics with chronic human infections [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have discussed that the presence or absence of bovine NAS isolates sharing the same niche as S. aureus may play a role in the host colonization [ 18 ], whereas others [ 37 , 52 ] observed a robust biofilm formation by NAS plus S. aureus in isolates from pigs, with no evident out-competition of one over the other species when growing in physical contact. According to Otto [ 53 ], in fact more than one mechanism could be involved in the biofilm formation and dispersion of staphylococci species, such as the bacterial social behavior (cooperation and/or competition), the molecular mechanism (e.g., bacterial signaling, coaggregation, or co-metabolism) [ 51 ], the immune response of the host (bovine mammary gland immune response), and both intrinsic and acquired traits of the isolates involved in the dual-species bacterial biofilms [ 54 ]. Nevertheless, as biofilms are extremely hard to eradicate by both the host and by antimicrobial therapies, these dual-species interactions would allow both species to persist in a colonizing state more robustly in one hand, but on the other hand would also provide a constant reservoir for possible S. aureus chronic infections [ 38 ].…”
Section: Discussionmentioning
confidence: 99%